How brightly does the glasma shine?: photon production off-equilibrium - Berges, Jürgen; Reygers, Klaus; Tanji, Naoto (Arxiv, 2017)
We present a parametric estimate of photon production at early times in heavy-ion collisions based on a consistent weak coupling thermalization scenario. We quantify the contribution of the off-equilibrium Glasma phase relative to that of a thermalized Quark-Gluon Plasma. Taking into account the constraints from charged hadron multiplicity data, the Glasma contribution is found to be significant especially for large values of the saturation scale.